ENGLISH IN THE EARLY YEARS: EXPLORING THE IMPLEMENTATION OF ENGLISH AS A MEDIUM OF INSTRUCTION (EMI) IN A PRIVATE SCHOOL IN DENPASAR - Putu Claudy Vernandia; Siti Mafulah; Lasim Muzammil; Muhammad Adi Nur Wakhid; Bagas Nirmansyah; Zacky Husain (International Journal of English Learning and Applied Linguistics (IJELAL), 2026)
English as a Medium of Instruction (EMI) in Indonesia has reached the primary level of education, where students face challenges in mastering academic content using a language they do not fully comprehend. This study employs a descriptive qualitative method to analyse the  implementation of EMI in one of primary schools in Denpasar, Bali. Besides, this study also explores teachers’ perceptions regarding its effectiveness in the process of learning and teaching. The data of this study were obtained from semi-structured interviews with eight selected teachers which were met the criteria as participants. Non-participant observation classroom and document analysis of existing international-based curricula like Cambridge textbooks were considered as supporting data. The results show that a flexible bilingual approach (translanguaging) strategy conducted by the teachers, where Bahasa Indonesia is used as a scaffolding tool to ensure students’ comprehension of complex ideas is more effective, rather than following a rule to only use English during the learning activities. Teachers are able to overcome the gap in language barriers by using multimodal strategies, creatively adapting international materials to fit the students’ level of proficiency, and using visual aids and digital media. Moreover, teachers who have high positive perceptions toward EMI, knowing it as a tool that is beneficial for both the acquisition of language and the mastery of subjects, despite admitting the constant cognitive difficulties for students.